EDUCATION ABOUT KNOWLEDGE NUTRITION ON LUNG FUNCTION IMPAIRMENT IN WORKERS AT PT X COAL - Lisa Septiana; Iriyani K; Ratih Wirapuspita Wisnuwardani (Jurnal Layanan Masyarakat (Journal of Public Services))
Mine workers are a group that is vulnerable to various health problems, particularly lung function disorders caused by dust exposure in the work environment. Nutritional knowledge plays a significant role in maintaining lung health. This community service aims to improve nutritional knowledge related to Occupational Safety and Health (K3) to prevent lung function disorders in mine workers at PT X Coal Division. The method used was action research with a cross-sectional approach involving 28 respondents. A structured questionnaire was employed as a pre-test and post-test instrument, consisting of 10 true-false items assessing knowledge about the importance of nutrition and the application of OHS principles in the workplace. Nutrition education was delivered in the form of interactive counselling sessions. Data were analysed using the Wilcoxon signed-rank test to determine differences in knowledge before and after the intervention. The results showed a significant improvement in knowledge: prior to counselling, 75% of respondents had moderate knowledge, whereas after counselling, 96.4% demonstrated good knowledge. This indicates that the nutrition education program was effective in enhancing workers' understanding of nutrition and occupational health. A continuous and structured counselling program is recommended to sustain awareness and encourage preventive behaviors among mine workers.